1998
DOI: 10.7182/prtr.1.8.3.y27m46071k304638
|View full text |Cite
|
Sign up to set email alerts
|

Texas non—donor-hospital project: a program to increase organ donation in community and rural hospitals

Abstract: Identifying and recovering donors from community and rural hospitals present a challenge to organ procurement organizations. A study of non-donor hospitals in the United States was undertaken at Johns Hopkins University, which identified 31 hospitals (in one service area) with the facilities to accommodate organ donation, though an organ donor had not been produced in 3 years. The purpose of this study was to determine whether donors could be produced from these hospitals. A large, geographically dispersed OPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The participants targeted in these interventions were mainly nurses and physicians. However, six of these studies involved hospital staff, without specifying which types of HPs were targeted [36,38,40,42,44,45]. Also, in six of the ten studies, the number of participants was not provided [36,37,41-44].…”
Section: Resultsmentioning
confidence: 99%
“…The participants targeted in these interventions were mainly nurses and physicians. However, six of these studies involved hospital staff, without specifying which types of HPs were targeted [36,38,40,42,44,45]. Also, in six of the ten studies, the number of participants was not provided [36,37,41-44].…”
Section: Resultsmentioning
confidence: 99%
“…This includes the intention to withdraw life‐sustaining treatment in patients (NICE, 2011). Six studies (Burris and Jacobs, 1996; Robertson, 1998; Shafer et al , 1998; Dickerson et al , 2002; Shafer et al , 2008; Graham et al , 2009) reported an increase in the number of donations when required referral was used in hospitals. Required referral is not standard practice in many critical care units and emergency departments and would require careful implementation.…”
Section: Identification Of Potential Organ Donorsmentioning
confidence: 99%